2019
DOI: 10.3390/su11102916
|View full text |Cite
|
Sign up to set email alerts
|

Internet’s User Perception of Corporate Social Responsibility in Hotel Services

Abstract: The objective of this study was to use the perceptions of internet users to analyse the effect of the social, economic and environmental dimensions of corporate social responsibility (CSR) implemented by hotel establishments in order to determine whether those dimensions are perceived by consumers. Our analysis was based on a sample, distributed by age, sex and province segments, obtained from the Andalusian population between 16 and 74 years of age who are users of travel websites (e.g., TripAdvisor, Booking)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
(87 reference statements)
1
10
0
1
Order By: Relevance
“…Its application to a sample of hotel managers, selected in the present research, gave back positive results. The results of this study are in accordance with the results obtained by García-Pozo et al [46]. They concluded that "customers of hotel services have an increasing interest in business attitudes that promote the greater involvement of hotel establishments in their environmental, social, and economic setting" (p. 10).…”
Section: Discussionsupporting
confidence: 91%
“…Its application to a sample of hotel managers, selected in the present research, gave back positive results. The results of this study are in accordance with the results obtained by García-Pozo et al [46]. They concluded that "customers of hotel services have an increasing interest in business attitudes that promote the greater involvement of hotel establishments in their environmental, social, and economic setting" (p. 10).…”
Section: Discussionsupporting
confidence: 91%
“…The PLS path modelling is a variance-based technique recommended in an early stage of theoretical development in order to test and validate exploratory models [87,88]. PLS was selected as it brings together three advantages; first, it is a nonparametric technique and, consequently, does not assume normality of the data and estimates least squares recursively; second, it works well with smaller sample sizes; third, it has a predictive role allowing for planning and future decision making [89][90][91][92]. PLS sample size requirements are more relaxed compared to covariance-based techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, several authors have shown that tourists are willing to give up a certain degree of comfort and luxury to support hotels that have adopted environmentally-friendly initiatives Manaktola & Jauhari, 2007) and even to make certain financial sacrifices (Kim et al, 2017;Yusof et al, 2017). In their work, Garc ıa- Pozo et al (2019) show that environmental commitment by hotel establishments, and therefore their greater environmental awareness, is highly relevant to Andalusian consumers. In contrast, other studies have demonstrated that, although consumers are aware of environmental issues, not all of them are familiar with the environmental measures implemented by hotels (Gil-Soto et al, 2019;Wang et al, 2018).…”
Section: Green Practicesmentioning
confidence: 99%